ANALISIS KESALAHAN EJAAN DALAM KARANGAN NARASI PADA SISWA KELAS V SEKOLAH DASAR KECAMATAN SUMEDANG SELATAN - Anggi Citra Apriliana; Avini Martini (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2018)
This study aims to uncover spelling errors (letter use errors, word writing, and punctuation use) of fifth grade students ofelementary schools in South Sumedang District, Sumedang Regency. To achieve this goal qualitative descriptive research iscarried out with steps: collecting data on students' language errors and conducting language error analysis. The researchsubjects were fifth grade students of Margacinta Elementary School, Manangga Elementary School, and Pasanggrahan IElementary School, South Sumedang District. The results of the study showed that there were errors in language in students'narrative essays which included spelling errors (letter usage errors, word writing, and punctuation errors). Spelling errors thatoften appear are errors in capital letters, incorrect writing of prepositions, errors in the use of punctuation, errors in writingwords that are not in accordance with the rules of the correct language, and errors in writing of particles. The largest number ofmisspellings is Manangga Elementary School with a number of spelling errors of 52 (43.33%) and the smallest number ofmisspellings, namely Margacinta Elementary School with 27 (22.5%) errors.